2018
DOI: 10.1016/j.jngse.2017.10.010
|View full text |Cite
|
Sign up to set email alerts
|

Resource potential of gas reservoirs in South Pakistan and adjacent Indian subcontinent revealed by post-stack inversion techniques

Abstract: Changes made as a result of publishing processes such as copy-editing, formatting and page numbers may not be reflected in this version. For the definitive version of this publication, please refer to the published source. You are advised to consult the publisher's version if you wish to cite this paper.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(21 citation statements)
references
References 40 publications
1
19
0
Order By: Relevance
“…It can be observed that the porosity varies from a maximum of 25% (red color) to minimum of 5% (pink color) along with the range of AI varying from 6000 to 13,000 (g/cc) × (m/s). Herein, it is important to point out that low AI layers are consistent with high porosity values over the entire field as compared to previous studies in the region [18]. However, in the middle of the reservoir interval (vertically), high porosity layer is visible but the values of AI is also high at this particular location.…”
Section: Reservoir Character (Porosity) Estimationsupporting
confidence: 85%
See 3 more Smart Citations
“…It can be observed that the porosity varies from a maximum of 25% (red color) to minimum of 5% (pink color) along with the range of AI varying from 6000 to 13,000 (g/cc) × (m/s). Herein, it is important to point out that low AI layers are consistent with high porosity values over the entire field as compared to previous studies in the region [18]. However, in the middle of the reservoir interval (vertically), high porosity layer is visible but the values of AI is also high at this particular location.…”
Section: Reservoir Character (Porosity) Estimationsupporting
confidence: 85%
“…Although complex and nonlinear relationship exists between the thinly layered media and seismic waveforms, SVM established nonlinear projection relationship to capture the thinly layered media from the seismic waveform. In contrast, the inverted AI from model-based or other traditional algorithms applied previously in the same dataset have not been good enough to capture the small lithological variations [18,19]. What is more, overall lateral and vertical variations in the resolution of AI estimated from traditional inversion algorithms was poor and resulted in discontinuity of seismic event.…”
Section: Reservoir Characterization From Seismic Datamentioning
confidence: 91%
See 2 more Smart Citations
“…A combination of wireline geophysical logging (Szabó and Dobrók, 2013) and an empirical dependence of coalbed methane content on rank of coal and depth position (Mullen, 1989) is another indirect approach for preliminary estimation of methane resources. Recently new approaches such as seismic methods (Ali et al, 2018) began to gain popularity for indirect assessments of gas content in coal bearing strata. However all indirect methods can predict potential amount of methane in coal bearing strata as a first approximation.…”
mentioning
confidence: 99%